INTERACTION OF L-CYSTEINE WITH DIMETHYL SULFOXIDE IN MILD CONDITIONS (Proceedings of the YSU B: Chemical and Biological Sciences, 2013)
Interaction of L-cysteine with DMSO in aqueous solutions was studied by FTIR spectroscopy. It is found that the processes involved are not limited by the solvation processes only, but a further oxidative conversion of L-cysteine to L-cystine takes place in mild conditions, separating dimethyl sulfide and water being other products of reaction.
Keywords: L-cysteine; L-cystine; FTIR spectroscopy